The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1152/ajpheart.00058.2014
|View full text |Cite
|
Sign up to set email alerts
|

High-fat, low-carbohydrate diet promotes arrhythmic death and increases myocardial ischemia-reperfusion injury in rats

Abstract: High-fat, low-carbohydrate diets (HFLCD) are often eaten by humans for a variety of reasons, but the effects of such diets on the heart are incompletely understood. We evaluated the impact of HFLCD on myocardial ischemia/reperfusion (I/R) using an in vivo model of left anterior descending coronary artery ligation. Sprague-Dawley rats (300 g) were fed HFLCD (60% calories fat, 30% protein, 10% carbohydrate) or control (CONT; 16% fat, 19% protein, 65% carbohydrate) diet for 2 wk and then underwent open chest I/R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 65 publications
5
22
0
Order By: Relevance
“…Similar cardiac alterations have been reported in obese mice fed a long-term high-fat diet [30]. However, in a 2-week study on rats no change in CD36 was reported, making the duration of diet intake interesting [31]. In the present study the expression of the gene encoding natriuretic protein A (ANP) was significantly lower in the LCHF group.…”
Section: Discussionsupporting
confidence: 86%
“…Similar cardiac alterations have been reported in obese mice fed a long-term high-fat diet [30]. However, in a 2-week study on rats no change in CD36 was reported, making the duration of diet intake interesting [31]. In the present study the expression of the gene encoding natriuretic protein A (ANP) was significantly lower in the LCHF group.…”
Section: Discussionsupporting
confidence: 86%
“…This effect is not entirely due to the effect on glucose oxidation, since it is independent of its effect on glucose uptake in the postischemic isolated working rat heart (48). The observed decrease in Akt phosphorylation in HFLCD under I/R, with no change in CHO oxidation compared with CONT diet, is consistent with our previous work finding that HFLCD did not alter expression of glucose uptake (GLUT4) and glucose oxidation genes under I/R (25). Thus the cardioprotective effects of insulin, and its impact on glucose uptake, appear to be at least partly uncoupled.…”
Section: Discussionsupporting
confidence: 91%
“…Population studies evaluating the impact of HFLCD on cardiovascular clinical outcomes have provided a range of results, with some finding favorable changes in cardiovascular disease risk factors (9,35,37), and others showing an increased risk of adverse outcomes in both animal (29) and human studies, including in the setting of myocardial infarction (23). Consistent with this latter finding, we have previously demonstrated that HFLCD (when eaten prior to experimental infarction) induced lower recovery of cardiac function, larger infarct size, and increased risk of death by pump failure and ventricular arrhythmias following coronary ligation myocardial ischemia-reperfusion (25). However, the mechanisms causing these impaired responses are not fully known.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Previous studies have revealed that HFD promoted arrhythmic death and increased myocardial ischemia-reperfusion injury in rats [30]. Moreover, other studies also detected increased vulnerability of atrial arrhythmia and impaired conduction velocity in HFD mice [31].…”
Section: Discussionmentioning
confidence: 92%